(untitled) (Journal of Global Arts Studies, 2023)
Background: The tomb of Yuhong of Sui Dynasty was excavated in Wangguo Village, Taiyuan City in 1999 by archaeologists from Shanxi Province. The only remaining burial equipment was the marble hall made of white marble. The stone hall was a wood-like three-open intermittent hill-top hall, consisting of a long flat square base, a central wall panel and a mountain top. Both inside and outside the stone hall are carved and painted, composed of 54 single images, rich in pattern content. The figures, costumes, utensils, Musical Instruments, dances, flowers and trees in the images are all related to Persia and Central Asian countries, and are also of great significance to the study of the Silk Road and the ancient East-West cultural exchanges.Objective: This study aims to explore the wine vessels depicted in the stone chamber images of the Yuhong Tomb in Taiyuan, with a focus on analyzing their cultural and artistic value. Through the study of the wine vessel images, the research seeks to reveal the artistic fusion in the cultural exchange along the Silk Road.Methods: The study utilizes image analysis and comparison with historical literature to categorize and analyze the wine vessels depicted in the stone chamber of the Yuhong Tomb in detail, with particular attention to the origins and evolution of wine vessel types such as Rhyton, Poluo, and tall-footed cups. It emphasizes their cultural significance and stylistic features.Results: The findings indicate that these wine vessels integrate artistic elements from Persia, Sogdiana, Rome, and indigenous Chinese culture, reflecting the significant role of the Silk Road in promoting artistic exchange and traditional absorption between different cultures.Conclusion: The study demonstrates that the wine vessels depicted in the stone chamber images of the Yuhong Tomb are not only artistic works but also evidence of cultural exchange. These discoveries are crucial for understanding the cultural interactions along the Silk Road and the contributions to China’s rich cultural heritage.